3dimensional coordinated search technique for a randomly located target. (2018) - ElHadidy, Mohamed Abd Allah; Teamah, Abd ElMoneim Anwar; ElBagoury, Abd AlAziz Hosni
This paper involves a new coordinated search model that determines a three dimensional randomly located target by using two searchers. Rather than finding the expected value the time for detecting the target in case of symmetric and asymmetric trivariate known distribution. We obtain the optimal search strategy that minimises the expected value of the detection time of the search to detect the target, assuming standard normal and skew standard normal distributions. An illustrative example has been given to demonstrate the applicability of this technique.